2019
DOI: 10.1093/jscr/rjz324
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic melanoma of the gallbladder presenting as polyp in acute cholecystitis

Abstract: Malignant melanoma is an aggressive neural crest cell-derived neoplasm with a propensity for metastasis to almost any organ. Gastrointestinal metastasis may manifest as gallbladder polyps. We report a case of metastatic malignant melanoma diagnosed in an 81-year-old male after cholecystectomy performed for acute cholecystitis. Cholecystectomy remains the standard of care for treatment of isolated gallbladder metastasis, especially in the setting of symptomatic disease. Mutation-directed chemotherapeutic and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Regarding sex, 67.2% of the patients were male (39 patients), whereas 32.8% were female (19 patients). The ratio between men and women was 3:1, suggesting a male predominance in the reported MMG population 6–43 …”
Section: Resultsmentioning
confidence: 95%
“…Regarding sex, 67.2% of the patients were male (39 patients), whereas 32.8% were female (19 patients). The ratio between men and women was 3:1, suggesting a male predominance in the reported MMG population 6–43 …”
Section: Resultsmentioning
confidence: 95%
“…Even if the surgical approach was different (4 patients had an open surgery, 6 had a laparoscopic procedure, and 1 had an endoscopic surgery that was converted to an open procedure), it is worth mentioning that, unlike for our patient, all surgeries were carefully planned and performed with oncological precautions. Of note, only 3 of the 11 favorable post-operative outcome patients had adjuvant immunotherapy [ 13 , 15 , 17 ]. Pivotal randomized control trials have shown that adjuvant immunotherapy could significantly increase recurrence-free survival in resected stage IV melanoma patients [ 9 , 10 ], possibly improving these already favorable outcomes post gallbladder resection.…”
Section: Discussionmentioning
confidence: 99%
“…This tumour can virtually metastasize to any organ of the body even years after diagnosis and it is characterized by various morphologic patterns that can mimic any type of neoplastic disease ranging from benign to malignant ones [ 13 ]. Metastasis usually spread via lymphatic system draining in the areas around the primary melanoma and via blood stream to distant sites, such as skin and soft tissues, lung, liver, brain and gastrointestinal tract [ 2 , 14 ]. Isolated metastasis of gallbladder are barely described, and mostly present in a widespread metastatic disease.…”
Section: Discussionmentioning
confidence: 99%